2016
DOI: 10.1515/helmin-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Hexabothriid monogeneans from the gills of deep-sea sharks off Algeria, with the description of Squalonchocotyle euzeti n. sp. (Hexabothriidae) from the kitefin shark Dalatias licha (Euselachii, Dalatiidae)

Abstract: SummarySharks (765 specimens from ten species) from the Mediterranean Sea off Algiers, Algeria, were examined for the presence of gill monogeneans. The following deep-sea sharks were investigated from 2009 to 2015: Centrophorus granulosus (27 specimens); Centrophorus uyato (39); Etmopterus spinax (67); Somniosus rostratus (19); Galeus melanostomus (189); Scyliorhinus canicula (261), Hexanchus griseus 3), and Dalatias licha (100). In addition, two pelagic shark species were examined: Alopias vulpinus (7), and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
“…This paper is a part of an ongoing effort to characterise the parasite biodiversity of fish of the southern shores of the Mediterranean Sea (Ayadi et al 2017;Boudaya and Neifar 2016;Bouguerche et al 2019;Chaabane et al 2015Chaabane et al , 2016aChaabane et al , b, 2017Chaari et al 2016;Kheddam et al 2016;Kouider El Ouahed-Amine 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since sequences of mitochondrial cytochrome c oxidase subunit I (COI) have proven reliable for distinguishing monogenean species [12] [13], we provide new sequences for both Microcotyle species. This paper is part of a project on the monogeneans of the south shores of the Mediterranean Sea [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%